Scratch-resistant and weather-resistant PBT composite material and preparation method thereof
A PBT composite material with titanium dioxide and zirconium phosphate enhances scratch and weather resistance, addressing the texture and performance gaps in existing sanitary ware materials, achieving high-density, ceramic-like bathroom products.
Patent Information
- Application Number
- CN202411481412.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Current materials used in the sanitary ware industry, such as urea-formaldehyde resin and PP, lack scratch resistance and weather resistance, and have a texture that differs significantly from ceramics, while PBT resin offers high potential but requires enhancement for better performance.
A PBT composite material is developed with titanium dioxide, a coupling agent, and zirconium phosphate, along with optional ultraviolet absorbers and antioxidants, to enhance scratch resistance, weather resistance, and texture, using a melt extrusion process with specific temperature and mixing conditions.
The PBT composite material achieves superior scratch resistance, excellent weather resistance, and a ceramic-like texture, with improved dispersibility and interface strength, suitable for bathroom products.
Smart Images

Figure CN119119695A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a scratch-resistant and weather-resistant PBT composite material and a preparation method thereof. Background Art
[0002] Polybutylene terephthalate (PBT) is one of the five general engineering plastics. It is a crystalline thermoplastic polyester with excellent scratch resistance, heat resistance, electrical insulation, processability, low water absorption and resistance to chemical solvents. It has been widely used in the fields of electronics, automobiles, and home appliance parts. With the continuous development of PBT modification methods, its uses are becoming more and more extensive.
[0003] The toilet accessories materials in the sanitary ware industry are currently mainly urea-formaldehyde resin, acrylic and PP materials. Urea-formaldehyde resin and acrylic are expensive, and PP materials have poor scratch resistance and weather resistance and low density, resulting in a texture that is far different from ceramics. Among general-purpose plastics and commonly used engineering plastics, PBT resin has a high application potential in the sanitary ware industry due to its high density, affordable price, and excellent scratch resistance and weather resistance. Therefore, it is of great value to develop a PBT composite material with excellent scratch resistance, weather resistance and good texture. Summary of the invention
[0004] Based on this, it is necessary to provide a PBT composite material, which has the characteristics of superior scratch resistance, excellent weather resistance and good texture, and can be mainly used in the bathroom industry, such as toilet covers, flush tank covers, and toilet connecting parts.
[0005] To achieve the above object, the present invention adopts the following scheme:
[0006] The first aspect of the present invention relates to a scratch-resistant and weather-resistant PBT composite material, comprising the following raw materials in parts by weight:
[0007]
[0008] The intrinsic viscosity of the PBT resin is 0.65-0.95 dL / g; the total weight of the PBT resin and the titanium dioxide is 100 parts.
[0009] Optionally, the invention further comprises 0.4 to 0.5 parts by weight of an ultraviolet absorber and / or 0.1 to 0.3 parts by weight of an antioxidant.
[0010] Optionally, the weight proportion of the titanium dioxide in the raw material is greater than 20%.
[0011] Optionally, the titanium dioxide is rutile titanium dioxide with a mesh size of 8000 to 1000 mesh.
[0012] Optionally, the coupling agent is at least one silane-type coupling agent.
[0013] Optionally, the zirconium phosphate is α-zirconium phosphate, including a mixture of Zr(HPO4)2·H2O and ZrO2.
[0014] Optionally, the ultraviolet absorber is at least one of salicylate, benzophenone, benzotriazole, substituted acrylonitrile, and triazine ultraviolet absorbers.
[0015] The antioxidant is at least one of hindered phenol antioxidants, hindered amine antioxidants, phosphate antioxidants, and thioester antioxidants.
[0016] In one embodiment, the antioxidant is a mixture of [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol (antioxidant 1010) and tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168), preferably in a weight ratio of 1:0.5 to 1.5.
[0017] The second aspect of the present invention relates to a method for preparing a scratch-resistant and weather-resistant PBT composite material, comprising the following steps:
[0018] Take PBT resin and dry it; stir and mix 10 to 30 parts by weight of titanium dioxide and 2 to 5 parts by weight of coupling agent;
[0019] Then add 70-90 parts by weight of the PBT resin and 5-10 parts by weight of zirconium phosphate and stir and mix; wherein the total weight of the PBT resin and the titanium dioxide is 100.
[0020] Optionally, the process parameters of the extruder for melt extrusion are: the temperature of zone 1 is 160-180°C, the temperature of zone 2 is 240-260°C, the temperature of zone 3 is 240-260°C, the temperature of zone 4 is 240-260°C, the temperature of zone 5 is 240-260°C, the temperature of zone 6 is 220-240°C, the temperature of zone 7 is 220-240°C, the temperature of zone 8 is 220-240°C, the die head temperature is 240-260°C, and the screw speed is 300-500rpm.
[0021] The third aspect of the present invention relates to the use of the above-mentioned scratch-resistant and weather-resistant PBT composite material in the preparation of bathroom products.
[0022] The principle of the present invention is as follows:
[0023] In order to prepare a scratch-resistant and weather-resistant PBT composite material, the present invention adopts a titanium dioxide-filled modified PBT solution. The titanium dioxide filler has a large density and strong hiding power. The filled and modified PBT material has a high density and an excellent texture similar to ceramics. In addition, due to the excellent matting performance of titanium dioxide, the weather resistance of the composite material can be greatly improved.
[0024] Moreover, the coupling agent and titanium dioxide are pre-mixed, the coupling agent and titanium dioxide fully interact with each other, and the coupling agent has amphiphilicity, which improves the dispersibility of titanium dioxide in the composite material and prevents poor performance and appearance of the composite material due to agglomeration of titanium dioxide.
[0025] At the same time, the use of PBT resin with a certain characteristic viscosity improves the fluidity of the material, strengthens the dispersion of titanium dioxide in the resin matrix, and improves the appearance of the material;
[0026] At the same time, zirconium phosphate is a new type of layered multifunctional mesoporous material with excellent lubrication properties. It can adhere to the secondary surface of the material to form a protective film, significantly improving the wear and scratch resistance of the material. Zirconium phosphate has a large specific surface area and has a high affinity for organic resins and inorganic fillers. It can greatly increase the interface strength between the resin and the inorganic filler, improve the dispersion of the inorganic filler in the resin, and improve the appearance of the composite material.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The PBT composite material of the present invention has the characteristics of superior scratch resistance, excellent weather resistance and good texture.
[0029] The details are as follows:
[0030] 1. The PBT composite material of the present invention has excellent scratch resistance, excellent weather resistance and excellent texture. The PBT modified by titanium dioxide filling has high density and strong hiding power. The PBT material after filling and modification has high density, ceramic texture and excellent weather resistance. Moreover, the coupling agent and titanium dioxide are pre-mixed and treated. The coupling agent has amphiphilicity, which improves the dispersibility of titanium dioxide in the composite material and prevents the poor performance and appearance of the composite material caused by the agglomeration of titanium dioxide. At the same time, the PBT resin with a certain characteristic viscosity is used to improve the fluidity of the material, strengthen the dispersion of titanium dioxide in the resin matrix, and improve the appearance of the material. At the same time, zirconium phosphate is a new type of layered multifunctional mesoporous material with excellent lubricating properties, which can adhere to the secondary surface of the material to form a protective film, significantly improving the wear resistance and scratch resistance of the material, and zirconium phosphate has a large specific surface area, has a high affinity for organic resin and inorganic filler, can greatly increase the interface strength between the resin and the inorganic filler, can improve the dispersibility of the inorganic filler in the resin, and improve the appearance of the composite material.
[0031] 2. The raw materials required for the PBT composite material of the present invention are all available on the market and are relatively easy to obtain.
[0032] 3. The preparation method of the PBT composite material of the present invention is simple and easy to operate, does not cause environmental pollution, and is easy to realize industrial continuous production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention is a process flow chart for preparing the scratch-resistant, weather-resistant and high-quality PBT composite material. DETAILED DESCRIPTION
[0034] The PBT composite material and the preparation method thereof of the present invention are further described in detail below in conjunction with specific embodiments.
[0035] The raw materials used in the embodiments of the present invention are as follows:
[0036] Polybutylene terephthalate (PBT), selected from Bluestar Nantong Xingchen Synthetic Material PBT 1084, with an intrinsic viscosity of 0.84±0.02dL / g;
[0037] Titanium dioxide, selected from DuPont R103 from the United States, with a mesh size of 8000 mesh;
[0038] The coupling agent such as γ-aminopropyltrimethoxysilane is selected from Zhejiang Feidian Chemical Co., Ltd.;
[0039] Ultraviolet absorbers such as UV234 are selected from BASF of Germany;
[0040] The zirconium phosphate used in this embodiment is α-zirconium phosphate, which is selected from Mianzhu Yaolong Chemical Co., Ltd.;
[0041] Antioxidants such as pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (antioxidant 1010) and tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168) are selected from Yixing Angel Synthetic Chemical Co., Ltd. A mixture of the two is used in the embodiment, and the ratio is by weight.
[0042] Embodiment 1:
[0043] The present embodiment provides a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0044]
[0045] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0046] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying; placing the titanium dioxide and coupling agent in a high-speed mixer (800 r / min), and stirring and mixing at room temperature for 30 minutes;
[0047] Step 2: Put the PBT resin, titanium dioxide, coupling agent (γ-aminopropyltrimethoxysilane), ultraviolet absorber (UV234), zirconium phosphate and antioxidant (antioxidant 1010: antioxidant 168 = 1:1) into a blender (300 r / min), and mix at room temperature for 5 minutes;
[0048] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 240°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 240°C, the temperature of zone 6 is 220°C, the temperature of zone 7 is 220°C, the temperature of zone 8 is 220°C, the die temperature is 240°C, and the screw speed is 300rpm. The properties of the composite material are shown in Table 2.
[0049] Embodiment 2:
[0050] The present embodiment provides a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0051]
[0052] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0053] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying; placing the titanium dioxide and coupling agent in a high-speed stirrer (1000 r / min), and stirring and mixing at room temperature for 30 minutes;
[0054] Step 2: Put the PBT resin, titanium dioxide, coupling agent (γ-aminopropyltrimethoxysilane), ultraviolet absorber (UV234), zirconium phosphate and antioxidant (antioxidant 1010: antioxidant 168 = 1:1) into a blender (500r / min), and mix at room temperature for 5 minutes;
[0055] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 240°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 240°C, the temperature of zone 6 is 220°C, the temperature of zone 7 is 220°C, the temperature of zone 8 is 220°C, the die temperature is 240°C, and the screw speed is 400rpm. The properties of the composite material are shown in Table 2.
[0056] Embodiment 3:
[0057] The present embodiment provides a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0058]
[0059] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0060] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying; placing the titanium dioxide and coupling agent in a high-speed stirrer (1000 r / min), and stirring and mixing at room temperature for 30 minutes;
[0061] Step 2: Put the PBT resin, titanium dioxide, coupling agent (γ-aminopropyltrimethoxysilane), ultraviolet absorber (UV234), zirconium phosphate and antioxidant (antioxidant 1010: antioxidant 168 = 1:1) into a blender (500r / min), and mix at room temperature for 5 minutes;
[0062] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 240°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 240°C, the temperature of zone 6 is 220°C, the temperature of zone 7 is 220°C, the temperature of zone 8 is 220°C, the die temperature is 240°C, and the screw speed is 400rpm. The properties of the composite material are shown in Table 2.
[0063] Embodiment 4:
[0064] The present embodiment provides a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0065]
[0066] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0067] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying; placing the titanium dioxide and coupling agent in a high-speed stirrer (1000 r / min), and stirring and mixing at room temperature for 30 minutes;
[0068] Step 2: Put the PBT resin, titanium dioxide, coupling agent (γ-aminopropyltrimethoxysilane), ultraviolet absorber (UV234), zirconium phosphate and antioxidant (antioxidant 1010: antioxidant 168 = 1:1) into a blender (500r / min), and mix at room temperature for 5 minutes;
[0069] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 240°C, the temperature of zone 4 is 240°C, the temperature of zone 5 is 240°C, the temperature of zone 6 is 220°C, the temperature of zone 7 is 220°C, the temperature of zone 8 is 220°C, the die temperature is 240°C, and the screw speed is 400rpm. The properties of the composite material are shown in Table 2.
[0070] Embodiment 5:
[0071] The present embodiment provides a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0072]
[0073] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0074] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying; placing the titanium dioxide and coupling agent in a high-speed stirrer (1000 r / min), and stirring and mixing at room temperature for 30 minutes;
[0075] Step 2: Put the PBT resin, titanium dioxide, coupling agent (γ-aminopropyltrimethoxysilane), ultraviolet absorber (UV234), zirconium phosphate and antioxidant (antioxidant 1010: antioxidant 168 = 1:1) into a blender (500r / min), and mix at room temperature for 5 minutes;
[0076] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 250°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 250°C, the temperature of zone 6 is 230°C, the temperature of zone 7 is 230°C, the temperature of zone 8 is 230°C, the die temperature is 250°C, and the screw speed is 500rpm. The properties of the composite material are shown in Table 2.
[0077] Embodiment 6:
[0078] The present embodiment provides a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0079]
[0080] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0081] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying; placing the titanium dioxide and coupling agent in a high-speed stirrer (1000 r / min), and stirring and mixing at room temperature for 30 minutes;
[0082] Step 2: Put the PBT resin, titanium dioxide, coupling agent (γ-aminopropyltrimethoxysilane), ultraviolet absorber (UV234), zirconium phosphate and antioxidant (antioxidant 1010: antioxidant 168 = 1:1) into a blender (500r / min), and mix at room temperature for 5 minutes;
[0083] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 250°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 250°C, the temperature of zone 6 is 230°C, the temperature of zone 7 is 230°C, the temperature of zone 8 is 230°C, the die temperature is 250°C, and the screw speed is 500rpm. The properties of the composite material are shown in Table 2.
[0084] Comparative Example 1:
[0085] The PBT resin used in this comparative example is a medium-viscosity resin with an intrinsic viscosity of 1.05±0.02 dL / g, and the other raw materials are the same as those in the embodiment.
[0086] This comparative example is a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0087]
[0088] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0089] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying; placing the titanium dioxide and coupling agent in a high-speed stirrer (1000 r / min), and stirring and mixing at room temperature for 30 minutes;
[0090] Step 2: Put the PBT resin, titanium dioxide, coupling agent (γ-aminopropyltrimethoxysilane), ultraviolet absorber (UV234), zirconium phosphate and antioxidant (antioxidant 1010: antioxidant 168 = 1:1) into a blender (500r / min), and mix at room temperature for 5 minutes;
[0091] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 250°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 250°C, the temperature of zone 6 is 230°C, the temperature of zone 7 is 230°C, the temperature of zone 8 is 230°C, the die temperature is 250°C, and the screw speed is 500rpm. The properties of the composite material are shown in Table 2.
[0092] Comparative Example 2:
[0093] The raw materials used in this comparative example are the same as those in the examples.
[0094] This comparative example is a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0095]
[0096] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0097] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying;
[0098] Step 2: Put the PBT resin, titanium dioxide, coupling agent (γ-aminopropyltrimethoxysilane), ultraviolet absorber (UV234), zirconium phosphate and antioxidant (antioxidant 1010: antioxidant 168 = 1:1) into a blender (500r / min), and mix at room temperature for 5 minutes;
[0099] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 250°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 250°C, the temperature of zone 6 is 230°C, the temperature of zone 7 is 230°C, the temperature of zone 8 is 230°C, the die temperature is 250°C, and the screw speed is 500rpm. The properties of the composite material are shown in Table 2.
[0100] Comparative Example 3:
[0101] The raw materials used in this comparative example are the same as those in the examples.
[0102] This comparative example is a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0103]
[0104] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0105] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying;
[0106] Step 2: Put the PBT resin, coupling agent (γ-aminopropyltrimethoxysilane), ultraviolet absorber (UV234), zirconium phosphate and antioxidant (1010:168=1:1) into a blender (500r / min), and mix at room temperature for 5 minutes;
[0107] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 250°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 250°C, the temperature of zone 6 is 230°C, the temperature of zone 7 is 230°C, the temperature of zone 8 is 230°C, the die temperature is 250°C, and the screw speed is 500rpm. The properties of the composite material are shown in Table 2.
[0108] Comparative Example 4:
[0109] The raw materials used in this comparative example are the same as those in the embodiment.
[0110] This comparative example is a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0111]
[0112]
[0113] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0114] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying;
[0115] Step 2: Put the PBT resin, titanium dioxide, ultraviolet absorber (UV234), zirconium phosphate and antioxidant (1010:168=1:1) into a mixer (500r / min), and mix at room temperature for 5 minutes;
[0116] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 250°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 250°C, the temperature of zone 6 is 230°C, the temperature of zone 7 is 230°C, the temperature of zone 8 is 230°C, the die temperature is 250°C, and the screw speed is 500rpm. The properties of the composite material are shown in Table 2.
[0117] Comparative Example 5:
[0118] The raw materials used in this comparative example are the same as those in the embodiment.
[0119] This comparative example is a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0120]
[0121]
[0122] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0123] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying; placing the titanium dioxide and coupling agent in a high-speed stirrer (1000 r / min), and stirring and mixing at room temperature for 30 minutes;
[0124] Step 2: Put the PBT resin, titanium dioxide, coupling agent (γ-aminopropyltrimethoxysilane), zirconium phosphate and antioxidant (antioxidant 1010:antioxidant 168=1:1) into a blender (500r / min), and mix at room temperature for 5 minutes;
[0125] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 250°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 250°C, the temperature of zone 6 is 230°C, the temperature of zone 7 is 230°C, the temperature of zone 8 is 230°C, the die temperature is 250°C, and the screw speed is 500rpm. The properties of the composite material are shown in Table 2.
[0126] Comparative Example 6:
[0127] The raw materials used in this comparative example are the same as those in the embodiment.
[0128] This comparative example is a scratch-resistant and weather-resistant PBT composite material, which is prepared from the following raw materials in parts by weight:
[0129]
[0130] The preparation method of the above-mentioned PBT composite material comprises the following steps:
[0131] Step 1: drying the PBT resin at 140° C. for 4 hours, and cooling to room temperature after drying; placing the titanium dioxide and coupling agent in a high-speed stirrer (1000 r / min), and stirring and mixing at room temperature for 30 minutes;
[0132] Step 2: Put the PBT resin, titanium dioxide, coupling agent (γ-aminopropyltrimethoxysilane), ultraviolet absorber (UV234), antioxidant (antioxidant 1010: antioxidant 168 = 1:1) into a blender (500 r / min), and mix at room temperature for 5 minutes;
[0133] Step 3: Add the mixed materials in step 2 into the hopper of a parallel twin-screw extruder, and melt extrude, cool, air dry, and pelletize. The process parameters are as follows: the temperature of zone 1 is 160°C, the temperature of zone 2 is 250°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 250°C, the temperature of zone 6 is 230°C, the temperature of zone 7 is 230°C, the temperature of zone 8 is 230°C, the die temperature is 250°C, and the screw speed is 500rpm. The properties of the composite material are shown in Table 2.
[0134] The following is a table of embodiments and comparative examples (Table 1):
[0135] Table 1 List of weight parts of raw materials for examples and comparative examples
[0136]
[0137]
[0138] The plastic samples prepared in the above embodiments and comparative examples were subjected to the following performance tests (the results are shown in Table 2):
[0139] Tensile properties: tested according to GB / T 1040.1-2006 standard, tensile rate 50mm / min;
[0140] Impact performance: tested according to GB / T 1843-2008 standard;
[0141] Scratch resistance: The cross scratch method is used to evaluate the scratch resistance of the material by comparing the color difference (△E) of the material before and after scratching;
[0142] Weather resistance: Tested according to GB / T 16422.3-1997 standard (exposure conditions: 1. Radiation temperature 50°C, irradiation time 5h, irradiation intensity 0.8W / m 2 , 2. Spray water on the blackboard at 20°C for 1 hour, 3. Aging for 200 hours) Evaluate the material weather resistance by comparing the color difference (△E) before and after aging;
[0143] Texture: Based on the visual spline appearance and feel comparison evaluation, five observers gave scores (0.0-12.0 points) through observation in the same environment, and the average score of the five people was taken. The appearance evaluation level from good to bad is bright (10.0-12.0 points), very good (8.0-9.9 points), excellent (6.0-7.9 points), good (4.0-5.9 points), fair (2.0-3.9 points), and poor (0-1.9 points).
[0144] Table 2 Performance list of examples and comparative examples
[0145]
[0146]
[0147] It can be seen from Examples 1 to 6 that the more titanium dioxide is added, the better the weather resistance of the PBT composite material is. However, since inorganic fillers are easy to agglomerate in organic resins, the increase in the amount of titanium dioxide added will lead to a deterioration in the appearance of the composite material; the more coupling agent is added, the better the appearance of the composite material; the more ultraviolet absorber is added, the better the weather resistance of the composite material; the more zirconium phosphate is added, the more the scratch resistance of the material is significantly improved, and the appearance of the composite material can be effectively improved. Taking the above factors into consideration, Example 6 has the best comprehensive performance.
[0148] Compared with Example 6, the PBT resin used in Comparative Example 1 is a medium-viscosity resin with higher viscosity and poor fluidity, which affects the dispersion of titanium dioxide in the resin matrix and causes the appearance of the composite material to deteriorate; the resin and the coupling agent in Comparative Example 2 have not been subjected to high mixing treatment, and the interface bonding between the resin and the coupling agent is insufficient, and the affinity of the coupling agent cannot be maximized, which affects the dispersion of the filler; Compared with Example 6, Comparative Example 3 does not add titanium dioxide, and the weather resistance of the composite material is significantly reduced, and the density is significantly reduced, and the texture of the material is significantly deteriorated; Compared with Example 6, Comparative Example 4 does not add a coupling agent, and the bonding strength between the organic resin and the inorganic filler is significantly reduced, the dispersion ability of titanium dioxide in the resin matrix is weakened, and titanium dioxide is easy to agglomerate. Polymerization leads to poor appearance; in Comparative Example 5 compared with Example 6, no UV absorber is added, the resin absorbs a large amount of UV light and undergoes oxidative degradation, resulting in discoloration of the material; in Comparative Example 6 compared with Example 6, no zirconium phosphate is added, the surface lubricity of the composite material is significantly reduced, and the bonding ability between the resin and the inorganic filler is reduced, resulting in significantly reduced scratch resistance and texture of the material; by comparison, it can be found that the addition of titanium dioxide, coupling agent, zirconium phosphate and UV absorber has no obvious effect on the toughness of the composite material; by adopting the scheme described in Example 6, the scratch resistance, weather resistance and texture of the PBT composite material prepared are significantly improved, and the beneficial effects of a PBT composite material with superior scratch resistance, excellent weather resistance and good texture are obtained.
[0149] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0150] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A scratch-resistant and weather-resistant PBT composite material, characterized in that: The invention comprises the following raw materials in parts by weight: The intrinsic viscosity of the PBT resin is 0.65-0.95 dL / g; the total weight of the PBT resin and the titanium dioxide is 100 parts.
2. The scratch-resistant and weather-resistant PBT composite material according to claim 1, characterized in that: The invention also comprises 0.4 to 0.5 parts by weight of an ultraviolet absorber and / or 0.1 to 0.3 parts by weight of an antioxidant.
3. The scratch-resistant and weather-resistant PBT composite material according to claim 1, characterized in that: The titanium dioxide is rutile titanium dioxide with a mesh size of 8000 to 1000 meshes.
4. The scratch-resistant and weather-resistant PBT composite material according to claim 1, characterized in that: The coupling agent is a silane coupling agent.
5. The scratch-resistant and weather-resistant PBT composite material according to claim 1, characterized in that: The zirconium phosphate is α-zirconium phosphate, including a mixture of Zr(HPO4)2·H2O and ZrO2.
6. The scratch-resistant and weather-resistant PBT composite material according to claim 2, characterized in that: The ultraviolet absorber is at least one of salicylate, benzophenone, benzotriazole, substituted acrylonitrile and triazine ultraviolet absorbers.
7. The scratch-resistant and weather-resistant PBT composite material according to claim 2, characterized in that: The antioxidant is at least one of hindered phenol antioxidants, hindered amine antioxidants, phosphate antioxidants, and thioester antioxidants.
8. A method for preparing a scratch-resistant and weather-resistant PBT composite material, characterized in that: The following steps are involved: Take PBT resin and dry it; stir and mix 10 to 30 parts by weight of titanium dioxide and 2 to 5 parts by weight of coupling agent; Then add 70-90 parts by weight of the PBT resin and 5-10 parts by weight of zirconium phosphate and stir and mix; wherein the total weight of the PBT resin and the titanium dioxide is 100. The mixed material is melt-extruded to obtain the scratch-resistant and weather-resistant PBT composite material.
9. The method for preparing the scratch-resistant and weather-resistant PBT composite material according to claim 8, characterized in that: The process parameters of the melt extrusion extruder are: the temperature of zone 1 is 160-180°C, the temperature of zone 2 is 240-260°C, the temperature of zone 3 is 240-260°C, the temperature of zone 4 is 240-260°C, the temperature of zone 5 is 240-260°C, the temperature of zone 6 is 220-240°C, the temperature of zone 7 is 220-240°C, the temperature of zone 8 is 220-240°C, the die head temperature is 240-260°C, and the screw speed is 300-500rpm.
10. Use of the scratch-resistant and weather-resistant PBT composite material according to any one of claims 1 to 7 in the preparation of sanitary products.
Citation Information
Patent Citations
Weather-resistant white master batch, weather-resistant polyester material and preparation methods of weather-resistant white master batch and weather-resistant polyester material
CN102492269A
Colorful and brilliant glass fiber reinforced polyester material and preparation method thereof
CN108690332A
Wear-resistant polymer composite material as well as preparation method and application thereof
CN113462151A
